Embolization - Chabrot, Pascal; Boyer, Louis (Springer London : Imprint: Springer, 2014)
Innovations in catheterization techniques and embolization agents have considerably contributed to the development of endovascular occlusion techniques in arterial and venous trunks as much as distal parenchymal capillar beds. Mini invasive therapies, endovascular embolization and chemo-embolization now constitute valuable therapeutic alternatives in various fields: on a purely palliative or on a curative basis in oncology,  but also in traumatology, functional diseases, and for the treatment of benign tumors, or when dealing with post-operative complications. As in-depth and detailed descriptions of these techniques are all ready available in specialized books, our ambition is to provide a basic handbook for the young vascular radiologists in training and a checklist for the more experienced interventional radiologists, by providing for each of the constantly increasing indications a synthetic approach of the technique and its expected results. The first part of this book relates to the tool box (the materials) and the procedure techniques as well as the physiopathological requirements for carrying out embolization; the second part is an analytical description of the main situations and anatomo-clinical strategies. This handy book should to be a valuable memory aid for clinicians and interventional radiologists, readily available in the multidisciplinary staff rooms and in angiography suites.